Determinants of Cashew Agroforestry Adoption Among Smallholder Farmers in the Gambia: Implications for Resilient Farming Systems - Bojang, Baseedy; Emang, Diana (Institut Pertanian Bogor (IPB University), 2025)
Although agroforestry effectively addresses uncertainty, risk, and shocks, its adoption is slow among rural smallholder cashew farmers in the Gambia. This study investigates the factors influencing cashew agroforestry (AF) adoption through a household survey of 250 farmers from seven villages in the Kombo East District, West Coast Region. The adoption determinants were analyzed using a logit regression model and grouped into five categories: a) household preferences, b) resource endowment, c) risk and uncertainty, d) biophysical factors, and e) institutional factors. The study identified 28 factors, including demographics, experience, wealth, environmental threats, awareness, support, and climate change, as significantly influencing AF adoption. Despite recognizing the potential benefits of AF, farmers face constraints such as insufficient funds, poor-quality seedlings, limited extension services, lack of farmland, and low climate awareness. This study’s findings offer important insights for addressing the slow adoption of cashew AF in the Kombo East district, with potential relevance for similar regions in the Gambia and beyond. It offers insights for developing policies and programs to promote and accelerate AF adoption, enhance resilience in local farming systems, improve adaptive capacity, and provide diverse livelihood and socioeconomic benefits.